ANALISIS BOOK TAX DIFFERENCES TERHADAP PERSISTENSI LABA DAN LABA AKRUAL SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Bety Pramitasari (Journal of Accounting and Investment, 2009)
The research aims at examining the role of book tax differences to the persistence of earnings and earnings of accruals as moderate variable. This research also include control variable, that is industial factor. The hypothesis alternative is (1a) large positive book tax differences influence to  the less persistence of earning; (1b) large negative book tax differences influence to the less persistence of earning; (2a) large positive book tax differences releated to earning of accruals caused the less persistence of earnings; (2b) large negative book tax differences releated to earning of accruals caused the less persistence of earnings. The sample of this reaserch was all companies listed Indonesian Stock Exchange (ISX) within the period of 2000-2006. The data ware collected using purposive sampling method, that is taked with based on specific.  The amount of the sample was 50 companies with 160 data to be analyzed. This statistic method used multiple regression. The results of this research showed that large positive (negative) book tax differences does not influence to the less persistence of earning. Large positive (negative) book tax differences releated to earning of accruals does not cause the less persistence of earnings. The conclusion of the research is information in book tax differences can not measure persistence of earnings and information in accrual of earnings in book tax differences can not measure persistence of earning, so the information in book tax differences can not use to measure future earning  performence.